A Descriptive Study on Reform Leadership Academy in the Transportation Office South Sulawesi Provincial Government - Wiryanto , Wisber (Recent Trends in Arts and Social Studies Vol. 1, 2023)
The goal of this research is to improve future Reform Leadership Academy (RLA) training. With the help of education and training for governance goals, bureaucratic reform is carried out in Indonesia through developing the skills of the state civil apparatus. RLA training is one style of instruction. The National Institute of Public Administration has organized this program for the five years. The post-training evaluation of alumni RLA was completed by superior, subordinate, colleague and customer. This study employs descriptive research methodologies. A sample of RLA alumni in the transportation office of the South Sulawesi Provincial Government was selected using a purposive sampling technique. In November 2018, information was gathered through a questionnaire and an interview with RLA alumni regarding the implementation of reform proposals. Additionally, the data collection process included the use of a qualitative analysis technique. The findings generally showed that RLA alums were far more capable of implementing innovation and problem-solving in their jobs and responsibilities. There was a strong correlation between RLA training materials and competencies. There was organizational support for alumni in carrying out new solutions begun in the form of policy, infrastructure, budgets, and human resources.